The Analysis of Traditional Motifs in the Form of Contemporary Inlay in Tehran - mehdi amraei; Morteza Afshar; Khashayar Ghazizade (هنر اسلامی, 2021)
Inlaid art has undergone alternations from the beginning of its existence in Iran until the present era. Companionship in inlaid art can be examined from several perspectives; the first is the association of this art with the nature of its raw materials, which takes on a diverse shape and form due to the characteristics of these materials; second, the role of wood art accompaniment as an art complement to inlaid art from the point of view of technique and procedure, however, the most significant of these are the effects of traditional patterns on inlaid art in terms of design and the developments that occur in the field of contemporary inlay and so far comprehensively has not been purposefully studied. This research is accomplished via a descriptive and analytical methods by the means of library data. The findings of the research indicate that these accompaniments have always been associated with remarkable innovations and developments in contemporary inlaid art, and this research focuses on the analysis of traditional motifs in contemporary inlays in order to achieve changes in the inlaid art by relying on the contemporary artworks of Tehran; in such a way that the influence of traditional motifs in achieving luxurious formulations can be achieved. It is certain that inlaid art, due to the inherent need for role and design, has continuously benefited from the combination of beautiful and executable designs and designs in each period throughout history, and in the contemporary period with artistic developments in Tehran and the presence of prominent artists in the capital. Art has also manifested itself with new, valuable and glorious innovations and formulations that are unprecedented in the history of Iranian inlay. Research aims: 1. A study of traditional motifs in Iranian inlaid art. 2. An overview on the widespread effects of designs on contemporary Iranian inlay. Research questions: 1. What is the role of traditional patterns in the "design" of the magnificent works of contemporary inlay? 2. How are the bases for using traditional motifs in contemporary inlay formed?